'When I Look I Am Seen, So I Exist to Change': Supplementing Honneth's Recognition Model for Social Work - Stanley Houston (Social Work & Society, 2015)
The subject of identity continues to attract widespread interest and debate in the social sciences. The nature of who we are, our potential to be different, and our similarity with others, underpins many present-day social issues. This paper contributes to this debate by examining critically the work of Axel Honneth on optimal identity-formation. Although broadly supporting Honneth's chief construct of inter-personal recognition, a gap in his thinking is highlighted and addressed through proffering a fourth dimension to his tripartite model. This additional dimension requires demonstrations of recognition that instil hope in the face of hardship and empower positive transformations in identity. The implications of this reworked model for social work are then considered in terms of a range of approaches that can be utilised to build flourishing identities characterised by self-esteem, self-confidence, self-respect and self-belief.